Integrasi Nilai Budaya Batak dalam Pembelajaran IPS untuk Menumbuhkan Karakter Siswa SD - Yosua Marasi Parningotan Siagian; I Wayan Kertih; I Wayan Lasmawan (STKIP Subang, 2025)
This study aims to describe the implementation of integrating Batak cultural values into Social Studies (IPS) learning to foster student character at SD Swasta YP HKBP Pematangsiantar, Siantar Selatan District. A descriptive qualitative approach was applied, involving IPS teachers, the school principal, and six selected students from grades IV and V. Data collection techniques included observation, semi-structured interviews, and documentation. The findings indicate that while learning still relies on general textbooks, teachers actively relate materials to local cultural values such as dalihan na tolu, Batak folktales, and the spirit of cooperation. Integration strategies include thematic discussions, inspirational storytelling, and contextual class projects. This approach positively impacts student character development, particularly in politeness, responsibility, and collaboration. The main challenges encountered involve limited cultural-based learning materials, lack of teacher training, and restricted instructional time. The study recommends developing thematic modules based on Batak culture, providing contextual teaching training for teachers, and fostering collaboration with parents and cultural figures as strategies to strengthen relevant and sustainable character education.